Quality Assurance in Rural Touristic Accommodations in Times of COVID-19 - Daniela PETRE; Elena TOMA (Communications of International Proceedings, 2021)
The COVID-19 pandemic lead to a decline in touristic activities in many European countries, including in Romania. The impact was even higher in rural areas were for many people sales from tourism were the only source of income. The rural boarding houses survived only due to their agricultural component which provided subsistence goods for the owners. Additionally, the managers from rural tourism had to face in 2020 the challenge of traveling restrictions and social distancing, even if there was nothing more safer for a tourist in pandemic times than a house in the middle of  “nowhere” or in remote locations. So, we started our research by trying to understand what is the level of quality of services  in the rural touristic boarding houses and what can be done to improve them. With this idea in mind, the main purpose of this paper was to identify what measures can be implemented in this pandemic times to assure the touristic activities continuity from the perspective of managers and administrators of rural touristic boarding houses. The research was based on 139 questionnaires completed between June and September 2020 in 28 villages, with a deeply rural characteristics, from Maramures County (Romania). The main results of our survey revealed that in this kind of small accommodation facilities the pandemic safety requirements can be easily implemented and there is no need to close them or to put them in the same category with other big HORECA facilities.
Keywords: Rural Tourism; Quality Assurance; COVID-19 Measures; Safety Measures